KOMUNIKASI PERSUASIF ANTARA KONSELOR DAN ORANG DENGAN HIV (ODHIV) DALAM PELAYANAN VCT DI PUSKESMAS WATUBELAH CIREBON - Manshur, Muhammad Iqbal (Universitas Swadaya Gunung Jati, 2024)
ABSTRACT Puskesmas Watubelah is one of the health services in the District of Cirebon that provides VCT (Voluntary Counselling and Testing) and PDP (Care, Support, and Treatment) services to ODHIV. Effective communication is essential in the VCT service in influencing HIV patients to comply with ARV drug consumption. This research is done to find out persuasive communication and the obstacles between the Counselor and ODHiv in VCT services in Pushesmas watubelah. The research was conducted from June to July 2024 in a culinary manner with a constructivist paradigm. Data is collected through participatory observations, interviews, and documentation. Based on the results of the research, persuasive communication between the Counselor and ODHIV is in line with the theory of persuasive communication on the Elaboration Likelihood Model and the persuasive theory on cognitive dissonance. HIV patients as ODHIV have a strong motivation with a central route to the processing of their information, so that the counselor can easily persuade the patient through effective communication. Keywords : Persuasive Communication, Counselor, Service VCT